Illegal fishing in Isla del Coco National Park: Spatial-temporal distribution and the economic trade-offs - González Andrés, Cristina (2020)
The Isla del Coco National Park, located on the Pacific coast of Costa Rica, is rich in biodiversity and has a high concentration of pelagic species. This high marine biodiversity makes the Isla del Coco National Park (PNIC) a very attractive place for illegal fishers. We analyzed a dataset covering 8 years (2003–2010) of patrol records from PNIC with the aim of determining, a) the spatial-temporal distribution of illegal fishing, b) other areas that could be prone to illegal fishing but are currently undetected, c) the most profitable areas for this activity and d) the economic trade-offs of this illegal activity in relation to potential gains and the costs. Residuals Autocovariate Generalized Additive Models (RAC-GAMs) were used to model the illegal fishing activity’s spatial distribution in relation to topographic, biological and temporal (quarter of the year) variables. The final RAC-GAM showed that bathymetry, distance from the coast, slope of the seabed, and yellowfin tuna and silky shark abundance were the most important predictors of this activity. Predictive maps suggest a major trend in the abundance of illegal fishing between the second and third quarters of the year in waters surrounding a seamount within the Park. Maps of the most profitable areas highlighted a specific risk location that should be intensively monitored. Overall, the potential gains from this activity outweigh the potential costs of being caught. Our findings provide useful information that can be used to optimize enforcement, deter illegal fishing and, consequently, increasing the conservation of the protected species.